Abnormal fronto-striatal intrinsic connectivity reflects executive dysfunction in alcohol use disorders. (June 2019) - Galandra, Caterina; Basso, Gianpaolo; Manera, Marina; Crespi, Chiara; Giorgi, Ines; Vittadini, Giovanni; Poggi, Paolo; Canessa, Nicola
Abstract: The neural bases of cognitive impairment(s) in alcohol use disorders (AUDs) have been explained either with the specific involvement of frontal regions mostly affected by alcohol neurotoxic effects, or with a global brain damage underlying different neuro-cognitive alterations. Novel insights into this issue might come from the analysis of resting-state brain activity, representing a baseline level of intrinsic connectivity within and between the networks underlying cognitive performance. We thus addressed the neural bases of cognitive impairment(s) in 22 AUD patients, compared with 18 healthy controls, by coupling resting-state f MRI with an in-depth neuropsychological assessment of the main cognitive domains. We assessed a relationship between AUD patients' cognitive impairment and two complementary facets of intrinsic brain functioning, i.e., intensity of activation and functional network connectivity, related to the strength of connectivity within and between resting-state networks, respectively. Alcoholic patients' decreased cognitive performance involved specifically an executive domain associated with attentional and working-memory tasks. This impairment reflected an abnormal relationship, in patients versus controls, between cognitive performance and the intensity of intrinsic activity in the dorsolateral prefrontal and striatal nodes of the executive control network. Functional connectivity between the same structures was positively correlated with executive performance in the whole sample, but significantly reduced in patients. The present data suggest that AUD patients' executive impairment reflects dysfunctional connectivity between the cortical and subcortical nodes of the networks underlying cognitive control on goal-directed behavior. This evidence provides a baseline for future studies addressing the abnormal neural architecture underlying cognitive impairment in AUDs and the outcome of rehabilitative treatment.